Pengaruh Pengalaman Kerja Dan Kompetensi Terhadap Kinerja Karyawan Departement Plastic Injection PT. Honoris Industry - Syihan Khoirun Nashirin; Sigit purwanto; Mohammad Jibriel Avessina (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2025)
This study aims to determine the effect of work experience and competence on employee performance. The sample used in this study This is a sample of 68 employees of the Plastic Injection Department of PT Honoris Industry and using random sampling method. sample selection with random sampling method. This research is a quantitative quantitative research, using multiple linear regression analysis methods, t tests and f tests which are then processed with the help of SPSS statistical software26. The results of this study indicate that work experience and competence have a partial and simultaneous influence on the performance of employees of the Plastic Injection Department of PT Honoris Industry.